Kesulitan Guru Mengembangkan Kecerdasan Kognitif Anak Usia Dini dalam Pembelajaran Online Selama Pandemic Covid-19 - Korlina Makulua (Institut Agama Kristen Negeri (IAKN) Ambon, 2021)
Unpreparedness in accepting the transformation of offline education into online is a major factor in the difficulty of accepting online learning. This causes children's acceptance of low learning concepts that cannot be separated from the role of the teacher. This paper aims to find and analyze the weak skills of teachers in managing online early childhood learning during the covid 19 pandemic at PAUD Anggrek Indah Galala 2. The research method used in this study was descriptive qualitative research. The findings indicate that the low cognitive intelligence of early childhood is caused by the lack of PAUD teachers' skills in managing and implementing online learning. Of the 2 teachers who teach, there is 1 teacher who can use and carry out online learning, and even then it is only limited to conveying learning by explaining, without presenting it in pictures on ppt. this creates boredom in the child, which ultimately has an impact on the child's lack of concentration to follow the teaching and learning process. As a result, children are less enthusiastic in participating in online learning. This has an impact on the lack of children's absorption of the material being taught. Of the 11 children, the average cognitive level achieved was at the level of starting to develop (MB) and already developing (SB) and some of them were not yet developed (BB). This data shows that the cognitive intelligence achieved by children has not reached the target of Developing according to Expectations (BSH). Research contributes to providing education for education actors who support the online learning process and other stakeholders in early childhood education in PAUD.Keywords: Cognitive intelligence, online learning